Improvement Student Learning Outcomes Through Online Learning Using Nearpod - Purba, Leony Sanga Lamsari (International Journal of Scientific Research and Management (IJSRM), 2024)
This research is a quantitative descriptive study with a one group pretest posttest research design. The population in this study were 61 public high school students in East Jakarta, and the sample used was 72 students. The data collection technique is to do a pretest and posttest using multiple choice questions that have been validated as many as 21 questions with options A, B, C, D and E. The results of data analysis, namely the hypothesis test paired sample test using SPSS 24, the results are ttable=1.66 < tcount =7.35 for df=71 indicates that the alternative hypothesis is accepted with sig.0.00 (